Evaluation of Childhood Posterior Fossa Malignant Tumors: A Single-center Study - Burak Eren; İlker Güleç; Nuri Serdar Baş (Bagcilar Medical Bulletin, 2020)

(untitled)
Objective:The aim of this study is to determine the clinical and radiological findings, early surgical results, and complication rates of children who were admitted to the neurosurgery clinic due to the posterior fossa malignant tumor.Method:The records of patients under the age of 18 who were diagnosed as malignant posterior fossa tumors in our clinic between 2011-2020 were scanned. The demographic features, symptoms, signs, surgeries, pathological results, and complications of the patients were recorded. Pre and postoperative neuroimaging of patients are examined; The location of the tumor, the presence of a residual tumor and of hydrocephalus were examined.Results:Thirty-three patients were identified, the median age of these children was 7. Among the symptoms of admission were headaches (57.6%) and gait disturbance (48.5%). Papilledema, ataxia, and nystagmus were also common. Six patients had preoperative cranial nerve palsy and 3 patients had hemiparesis. Preoperative hydrocephalus was present in 66.7%. The most common tumor type was medulloblastoma (39.4%). The rate of high-grade tumors among the operated tumors was 66.7%. Seven of the resected tumors had invasion into the brain stem. Tumor resection was performed in 24 patients, in 12 patients total resection was achieved. Tumor surgery was not performed in patients with diffuse pontine glioma. External ventricular drainage (EVD) was inserted in 30.3% of all patients. Only 4 of them needed ventriculoperitoneal (V-P) shunt. High-grade tumors had a higher risk of complications than low-grade tumors (p=0.038). The complication rate was high in totally removed tumors (p=0.034). The most common complication was CSF fistula (16.7%). Three patients with EVD had signs of infection. Three patients had a hematoma at the postoperative tumor site. Hydrocephalus developed in two patients without EVD and V-P shunts were inserted to these patients. Four of 6 patients with V-P shunt inserted had postoperative intraventricular blood. Postoperative hemiparesis was observed in two patients without previous weakness. Three patients (12.5%) had mutism and one patient had dysarthria. Two patients had pneumonia during intensive care follow-up and one of these children died two months later.Conclusion:In children with posterior fossa malignant tumors; We found that a high degree of the tumor, brainstem invasion, complete removal of the tumor, and presence of postoperative blood in the ventricle increase the risk of complications.